Analysis of Employee Training Needs Based on Performance Evaluation at the Regional Disaster Management Agency of Wonogiri - Pawestri, Intan; Wijiastuti, Sri; Dwanita Widodo, Zandra; Ramadhan, Dwinanda Ripta (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to describe the implementation of employee performance evaluation and its use as a foundation for determining training needs within the Regional Disaster Management Agency (BPBD) of Wonogiri Regency. This research employs a qualitative approach with in-depth interviews conducted with the Secretary of BPBD as the key informant. The findings reveal that performance evaluations are conducted systematically, using indicators such as attendance, discipline, and target achievements. These evaluations serve as the basis for developing training programs, although several challenges remain, such as budget limitations, frequent staff rotations, and lack of sustainable training. Key competencies that require enhancement include disaster technical skills, intersectoral communication, digital literacy, and field leadership. This study recommends improvements in the evaluation system, strengthening simulation-based training, and involving employees in the planning of training programs.